The Assessment of Groundwater Availability in Sedimentary Environments Using the Electrical Resistivity Method: A Case of Ekpoma and Its Environs, Southern Nigeria - Endurance Idiahi; Kola Abdul Nafiu Adiat; Kesyton Oyamenda Ozegin; Samuel Obomheile Salufu; Stephen Adebayo; Ayokunle Adewale Akinlalu (Indonesian Journal of Earth Sciences, 2023)
Groundwater resources are an ephemeral aspect of the ecosystem, especially in the university town of Ekpoma, where the issue of severe water shortages brought on by failed or unproductive boreholes has lingered over time. This study makes an effort to thoroughly define the groundwater-bearing zones and estimate their thicknesses and depths in order to identify the cause(s) of groundwater scarcity in Ekpoma and its peri-urban area. In order to accomplish the objectives of the work, fifteen (15) Vertical Electrical Soundings (VES) were conducted across the study location, leveraging Schlumberger electrode array, with current electrode spacing varying from 5.00 to 550.00 m. The results show there were five distinct geoelectrical strata identified: top soil, clayey sandstone, sand, consolidated sandstone, and unconsolidated sandstone. The unconsolidated sandstone layer constituted the aquifer units in the area, whose depth ranges between 103.00 m and 258.00 m. Besides, this study showed that there is strong indication/evidence of saturation of the aquifer identified in the Imo Shale Formation surrounding Irrua with highly porous and permeable materials atop it, justifying the region's highly productive wells and boreholes. The aquifers delineated in and around the Ekpoma community, on the other hand, have relatively high resistive values (3404.20–5303.00 ?m), indicating less saturation, and are equally overlain by less porous and permeable materials, establishing why Ekpoma (located within the Bende-Ameki and Ogwashi Asaba Formations) has a perennial groundwater shortage.  The shallow aquifer units in the area of study were discovered to be rather thin, with the majority having a thickness of less than 30 m, making them less sustainable for long-term groundwater abstraction and resulting in failed boreholes in most portions of Ekpoma town. The study indicates that the groundwater prospects of Ekpoma and its environs are poor, and deep boreholes reaching a minimum depth of 250.00 m should be drilled since it is sustainable due to its significant thickness to serve the Ekpoma community and its environs. The present investigation findings can aid in improving knowledge of underlying geological conditions, evaluating the feasibility of the researched area for predicted urban and economic development, and sustaining water supply for connected activities.